STABILITAS DINAR EMAS DAN NILAI TUKAR RUPIAH TERHADAP INFLASI DI INDONESIA - Marlia Marlia (Department of Development Economics, Universitas Sriwijaya, 2014)
This research was aimed at identifying the influence of the stability of dinar gold and fiat money and inflation in Indonesia. It used the secondary data published in reports of Central Statistics Bureau, Bank Indonesia and London Stock Exchange in the period of 1970-2010. It consisted of data on Currency, Gross Domestic Products, Exchange Rates, Dinar gold and Inflation. It was analyzed by the application of Error Correction Model (ECM) method. The regression analysis shows three important points : (1) in the short term range, the total currencies, fiat money and dinar gold significantly influenced on the inflation; (2) growth of currencies and Gross Domestic Products were high in the fiat money model than that in the dinar gold model and (3) the degree of dinar gold stability on fi the inflation was better than that of the fiat money. Keywords: Dinar gold, Fiat Money, Inflation, Error Correction Model